2008
DOI: 10.1093/annonc/mdm480
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory breast cancer in Tunisia in the era of multimodality therapy

Abstract: Tunisian patients with IBC have particular epidemiologic characteristics, with earlier disease and context of overweight and obesity, but prognostic factors are similar to those reported in the literature. Hormone therapy seems to improve patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 28 publications
6
56
1
Order By: Relevance
“…There were three studies from each of Australia [79, 95, 96], Korea [97, 98] and China [99101]; two studies from Japan [71, 102]; one study from Tunisia [103] and four international studies [19, 104106]. Study size ranged from 96 [107] to 24 698 patients [97].…”
Section: Resultsmentioning
confidence: 99%
“…There were three studies from each of Australia [79, 95, 96], Korea [97, 98] and China [99101]; two studies from Japan [71, 102]; one study from Tunisia [103] and four international studies [19, 104106]. Study size ranged from 96 [107] to 24 698 patients [97].…”
Section: Resultsmentioning
confidence: 99%
“…Our study reveals a direct relationship of cancer cells with pathogenic bacteria, suggesting a TLR2-mediated mechanism in bacterial infection-associated human breast cancer metastasis. Since many cancer patients with weaken immune systems appear to be susceptible to bacterial infection and surgical contamination and there are always sporadic serious or light cases of surgical infection in clinic every year[3], [5], [49], our findings pointed importance of antibiotic therapy to treat breast tumor with bacterial infection especially of Staphylococcus aureus, a notable drug-resistant pathogen that easily occur in clinic. In addition, as some bacterial vaccine and adjuvant used in cancer treatment usually contain TLR2 agonist, this study is also relevant to genetic strategy for bacterial vaccine and adjuvant design in cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In two phase I studies reported at the 2008 ESMO meeting, axitinib was combined with a variety of chemotherapy regimens including FOLFOX and FOLFIRI in gastrointestinal malignancies and taxane-, capecitabine-, or gemcitabine-based treatments in a variety of solid malignancies. In both studies, the pharmacokinetics were not affected by the addition of chemotherapy and the toxicities were not increased 18,19. More involved studies have also explored axitinib chemotherapy combinations with other new agents including a PDGFR inhibitor CP-868,596 combined with docetaxel and axitinib.…”
Section: Outcomes Achieved In Clinical Developmentmentioning
confidence: 99%